Identifying Major Factors of Poultry Production as Sustainable Enterprise among Farmers Using Improved Methods in Rural Nigeria - Jaafar-Furo, M.R.; Gabdo, B.H. (International Journal of Poultry Science, 2010)
Investigations were conducted in 2006 with the primary aim of determining the major factors of improved methods of poultry production in Adamawa State, Nigeria. Purposive and random sampling methods were applied in selecting eight (8) and eighty (80) Local Government Areas and respondents, respectively. Data were analyzed using descriptive statistics and correlation analysis. Results indicated that adult males who produced within the medium-scale were the majority. Major factors that most influenced improved poultry production identified include land, labour, feeds and other investment expenses. Of the constraints that thwart production in the area, absence of poultry farmer education (100%), inadequacy of ready market for poultry and poultry products (98.8%), lack of institutional support (97.5%) and high cost of feeds (96.3%) were most reported. As a matter of policy, agencies that intend to use improved methods of poultry production for rural empowerment should not only address these constraints but also target the large producers in these rural areas, known as the women. This is the only way sustainability would be maintained.